REDUCING AFFECTIVE FILTER IN SECOND LANGUAGE ACQUISITION THROUGH SUGGESTOPEDIA - Kobilova, Makhfuza Sherali kizi (Educational Research in Universal Sciences, 2023)
Recent researches has been carried out in order to find out the reasons of the success and failure of the language acquisition. As Stephan Krashen proposed that there are learning hypothesis and one of them which is named Affective filter has enormous impact on SLA. Therefore, this study reveals the ways of reducing affective filter through Suggestopedia. Since anxiety, motivation and self confidence are considered as contributory factors of the affective filter, three observations are demonstrated to achieve low level of affective filter.